If x-y=8,find the value of y when x=3

QUESTION POSTED AT 20/02/2020 - 11:18 PM

Answered by admin AT 20/02/2020 - 11:18 PM

3-y=8
-y=8-3
y=-5
so just try to re arrange the equation  to find the value for the variable
Post your answer

Related questions

The quotient of x and 3 is less than or equal to 5

x/3 \leq 5

ANSWERED AT 28/03/2020 - 12:32 PM


QUESTION POSTED AT 28/03/2020 - 12:32 PM

1) 2x+8y=20 y=2 2x+8(2)=20 2) x=5 2x+y=10 2(5)+y=10 3) 5x-2y=3 y=2x 5x-2(2x)=3 4) 2y+x=-15 x=3y 2y+(3x)=-15 5) 4x+7y=19 y=x+9 4x+7(x+9)=19 6)y=6x+11 2y-4x+14 2(6x+11)-4x+14 7)2x-8y=6 y=-7-x 2x-8(-7-x)=6 8) x=2y-1 3x-2y=-3 3(2y-1)-2y=-3 what is the process and what x and y equal

If they give you what one variable is, you can plug it into the equation and use algebra to solve it. So:

1)2x=4 -> 4/2 = 2 so x=2

2) y=0

3) x=3

4) 2y + (3*3y) = -15
11y=-15 
y = -15/11

5) 4x + 7x + 63 = 19
11x = -44
x = -4

ANSWERED AT 28/03/2020 - 12:21 PM


QUESTION POSTED AT 28/03/2020 - 12:21 PM

Which statement is true for log3(x+1)=2 x+1=3^2 x+1=2^3 2(x+1)=3 3(x+1)=2

Therefore, x/(x-2) = 3. so, x = 3

ANSWERED AT 28/03/2020 - 12:16 PM


QUESTION POSTED AT 28/03/2020 - 12:16 PM

7e-m-4w if e=3, m=–8, w=1?9x-3y-f if X=3, Y=1, F= –8?–b - 4x +7g if B=2, X= 4, G=5??

Answer:


Step-by-step explanation:


ANSWERED AT 28/03/2020 - 12:06 PM


QUESTION POSTED AT 28/03/2020 - 12:06 PM

Solve the equation. 6 = 2(x + 8) - 5x A. 2/3 B. 3 1/3 C. - 2/3 D. -3 1/3

The correct answer is B.

ANSWERED AT 28/03/2020 - 11:46 AM


QUESTION POSTED AT 28/03/2020 - 11:46 AM

Okay so I'm in Advanced functions and Modeling in math in an online class and it's really stressing me out. So if you answer me you will have to be patient so i can learn because i'm not the best at math. Okay so- Given: f(x) = x - 7 and h(x) = 2x + 3 Write the rule for h(f(x)). I do not know how to do this and i'm in one classroom all day with someone who doesn't know math so... help?

You start from in to out, so in the case of h (f (x)) we start by substituting f (x)

By substituting f (x) you get h (x-7)
Now substitute x-7 in x's in the function h (x)
2x+3 will be 2 (x-7)+3
Therefore, h (f (x)) is 2x-14+3 which is 2x-11

ANSWERED AT 28/03/2020 - 11:18 AM


QUESTION POSTED AT 28/03/2020 - 11:18 AM

Urgant !! 3(2x-4) - 6(x-3) please provide explanation

3 (2x-4)-6 (x-3)
Distribute by multiplication 3 to both 2x and -4
And distribute by multiplication -6 to both x and -3

6x-12-6x+18
Add like terms

6

ANSWERED AT 28/03/2020 - 11:17 AM


QUESTION POSTED AT 28/03/2020 - 11:17 AM

Y=yx^3-3x+2 Find the intervals where the function is concave up or down and inflection points

\bf y=yx^3-3x+2\impliedby \textit{using implicit differentiation}
\\\\\\
\cfrac{dy}{dx}=\cfrac{dy}{dx}x^3+y3x^2-3\implies \cfrac{dy}{dx}-\cfrac{dy}{dx}x^3=3yx^2-3
\\\\\\
\cfrac{dy}{dx}(1-x^3)=3yx^2-3\implies \boxed{\cfrac{dy}{dx}=\cfrac{3yx^2-3}{1-x^3}}\\\\
-----------------------------\\\\
\cfrac{dy}{dx}=\cfrac{3yx^2-3}{1-x^3}\impliedby \textit{using the quotient rule}
\\\\\\
\cfrac{dy^2}{dx^2}=\cfrac{3[2xy+x^2\frac{dy}{dx}(1-x^3)]-(3x^2y-3)(-3x^2)}{(1-x^3)^2}
\\\\\\


\bf \begin{cases}
3[2xy+x^2\frac{dy}{dx}](1-x^3)\implies \left[6xy+6x^2\cdot \frac{3yx^2-3}{1-x^3}\right](1-x^3)\\
6xy-6x^4y+18x^4y-18x^2
\\
----------------\\
(3x^2y-3)(-3x^2)\implies -9x^4y+9x^2\\
\qquad -(9x^4y+9x^2)
\end{cases}
\\\\\\
\cfrac{dy^2}{dx^2}=\cfrac{6xy-6x^4y+18x^4y-18x^2+9x^4y+9x^2}{(1-x^3)^2}
\\\\\\
\boxed{\cfrac{dy^2}{dx^2}=\cfrac{6xy+21x^4y-9x^2}{(1-x^3)^2}}

so hmmm since it's implicit differentiation, you'd get a function in x,y terms so. hmm if we check the graph of that second derivative, it seems to be asymptotic at x = -1, meaning an inflection point, from the denominator equaling 0

and it has an x-intercept at the origin, x = 0, another inflection point

now, the graph of the second derivative, from  x > 0, the value for "y" is positive all the way, with a horizontal asymptote at y  = 0
meaning the original function f(x) is concave UP  at x > 0

now, when -1 < x < 0, the value of "y" drops to the negatives, thus is concave DOWN  at -1 < x < 0

and if we pass the asymptotic inflection point of x = -1, to the left
x < -1, the value of "y" is on the positives, thus concave UP on that region

ANSWERED AT 28/03/2020 - 11:01 AM


QUESTION POSTED AT 28/03/2020 - 11:01 AM

Match each given domain of the function f(x)=x/2.5 with its corresponding range. A. {40,45,50,55,60} B. {52,56,63,67,71} C. {37,46,49,55,57} D. {44,51,59,66,67} 1. {20.8,22.4,25.2,26.8,28.4} 2. {16,18,20,22,24} 3. {17.6,20.4,23.6,26.4,29.2} 4. {14.8,18.4,19.6,22,22.8}

Domain A matches Range 2  because 

40/2.5 = 16 , 45/ 2.5 = 18   and so on  -all 5 work ou.

If you do the same calculations for B, C and D you'll get the correct answers

It looks like Domain B matches Range 1:-  52 / 2.5 =  20.8, 56/2.5 =  22.4  

- I think I can leave you to finish this off .

ANSWERED AT 28/03/2020 - 11:00 AM


QUESTION POSTED AT 28/03/2020 - 11:00 AM

Which of the following inequalities is best represented by this graph? x − 2y > 3 x − 2y < 3 2x − y > 3 2x − y < 3

#3. Plugging the point (3,0) into any of the equations except the third one gives an invalid answer. 

ANSWERED AT 28/03/2020 - 10:53 AM


QUESTION POSTED AT 28/03/2020 - 10:53 AM

An equation is shown below: What is the solution to the equation? A) x = 1 B) x = 3 C) x = 5 D) x = 8

Hmm... I think the answer is C) x = 5. Have a great day!!

ANSWERED AT 28/03/2020 - 10:49 AM


QUESTION POSTED AT 28/03/2020 - 10:49 AM

What is the Value of the rational expression below when X is equal to 3? 15-x over 9-x (15-x/9-x) A) 3 over 2 (3/2) B) 5 over 3 (5/3) C) -2 D) 2

First, you would have to plug 3 into the equation
15-(3)/9-(3)
Then do the math
12/6
This can be simplified, since 12 and 6 are divisible by 6, which is their greatest common factor
2/1
So the answer is D. 2

Hope this helps!

ANSWERED AT 28/03/2020 - 10:47 AM


QUESTION POSTED AT 28/03/2020 - 10:47 AM

A student solves the following equation for all possible values of x: 8/x+2 = 2/x-4 His solution is as follows: Step 1: 8(x – 4) = 2(x + 2) Step 2: 4(x – 4) = (x + 2) Step 3: 4x – 16 = x + 2 Step 4: 3x = 18 Step 5: x = 6 He determines that 6 is an extraneous solution because the difference of the numerators is 6, so the 6s cancel to 0. Which best describes the reasonableness of the student’s solution? a) His solution for x is correct and his explanation of the extraneous solution is reasonable. b) His solution for x is correct, but in order for 6 to be an extraneous solution, both denominators have to result in 0 when 6 is substituted for x. c) His solution for x is correct, but in order for 6 to be an extraneous solution, one denominator has to result in 0 when 6 is substituted for x. d) His solution for x is incorrect. When solved correctly, there are no extraneous solutions

The correct answer is:
C) his solution for x is correct, but in order for 6 to be an extraneous solution, one denominator has to result in 0 when 6 is substituted for x.

Explanation:
To solve this rational equation, we cross multiply:
8*(x-4)=2*(x+2).

Using the distributive property, we have
8*x-8*4=2*x+2*2;
8x-32=2x+4.

Subtract 2x from each side:
8x-32-2x=2x+4-2x;
6x-32=4.

Add 32 to each side:
6x-32+32=4+32;
6x=36.

Divide both sides by 6:
 \frac{6x}{6} = \frac{36}{6} ;
x=6.

Extraneous solutions are solutions that come about in the problem but are not valid solutions to the problem; the only values of x that would give this sort of answer are -2 and 4, since these are the two values that would make one of the denominators 0 (we cannot divide by 0).

ANSWERED AT 28/03/2020 - 10:40 AM


QUESTION POSTED AT 28/03/2020 - 10:40 AM

(1 ÷ x- 1)+(2÷ x+2)=(3÷2) solve and check for extraneous solutions

 \frac{1}{x-1}+ \frac{2}{x+2}= \frac{3}{2}
\frac{1(x+2)}{(x-1)(x+2)}+ \frac{2(x-1)}{(x+2)(x-1)}= \frac{3(x-1)(x+2)}{2}
\frac{x+2+2(x-1)}{(x-1)(x+2)}= \frac{3(x-1)(x+2)}{2}
\frac{x+2+2x-1}{(x-1)(x+2)}= \frac{3(x-1)(x+2)}{2}
\frac{3x+1}{(x-1)(x+2)}= \frac{3(x^2+x-2)}{2}
\frac{}{(x-1)(x+2)}= \frac{3x^2+3x-6)}{2}
\frac{3x+1}{(x^2+x-2)}= \frac{3x^2+3x-6)}{2}
\frac{2(3x+1)}{2(x^2+x-2)}= \frac{3x^2+3x-6)(x^2+x-2)}{2(x^2+x-2)}
\frac{2(3x+1)}{2(x^2+x-2)}-\frac{3x^2+3x-6)(x^2+x-2)}{2(x^2+x-2)}=0
\frac{2(3x+1)-3x^2+3x-6}{2(x^2+x-2)}=0

this will be continued

ANSWERED AT 28/03/2020 - 10:18 AM


QUESTION POSTED AT 28/03/2020 - 10:18 AM

Which point is on the graph of f(x) = 3 • 4x? a.(12,1) b(0,12) C(0,0) d(1,12)

Its C (0,0) as the Graph indicated

ANSWERED AT 28/03/2020 - 10:15 AM


QUESTION POSTED AT 28/03/2020 - 10:15 AM

PLEASE HELP!!!!! 1. Determine the number of solutions for the equation 1 - 3(x - 2) = 7 - 3x A. infinite solutions B. no solutions C. one solution 2. Solve the following and show all work. The length of a rectangle is 4 less than 3 times the width. If the perimeter is 40, find the dimensions of the rectangle. 3. Solve the following and show all work. Jim is 5 years older than Cindy. 4 years ago, the sum of their ages was 21. Find each of their ages now. 4. Solve the inequality below and select the best explanation of its graph. -8+7r>10r-23 A. Open circle on 2 and line pointing to the left. B. Open circle on 5 and line pointing to the left. C. This is an incorrect answer. Have a nice day! D. Open cirle on 5 and line pointing to the right. 5. Use an inequality to solve the following problem. Show all work. Rita plans to spend at most $115.00 on a skirt and two blouses. She bought the two blouses for $38.95 each. How much can she spend on the skirt?

Let x = the width

it says, "The length of a rectangle is 4 less than 3 times the width." write that as: 
L = 3x - 4

If the perimeter is 40, find the dimensions of the rectangle.

We know: 2L + 2W = 40

Substitute (3x-4) for L and x for W
2(3x-4) + 2x = 40

6x - 8 + 2x = 40; multiplied what's inside the brackets

6x + 2x = 40 + 8; do some basic alegbra to find x; (added 8 to both sides)

8x = 48

x = 48/8

x = 6 which is the width

It said that L = 3x - 4, therefore:
L = 3(6) - 4
L = 18 - 4
L = 14; is the length

Check our solutions in the perimeter:
2(14) + 2(6) =
28 + 12 = 40

ANSWERED AT 27/03/2020 - 01:06 PM


QUESTION POSTED AT 27/03/2020 - 01:06 PM

Given that 12 , 3 is on the graph of f(x) find the corresponding point for the function

(12,24)
Hope it helps love.
-Joker7721

ANSWERED AT 27/03/2020 - 01:05 PM


QUESTION POSTED AT 27/03/2020 - 01:05 PM

Solve the following system. x^2/25+y^2/100 = 1 a {(3, 4), (-3, 4)} b {(4, 3), (-4, 3)} c {(0, -10), (0, 10)} d {(-5, 0), (5, 0)}

X²/25 + y²/100 =1
4x²/100+ y²/100 =1
4x²+y²=100
y²=100- 4x²
If x=0, y²= 100, y = ±10
c{(0,-10),(0,10)}
If y=0, 4x²= 100, x²=25, x=±5
d {(-5,0),(5,0)}

ANSWERED AT 27/03/2020 - 10:05 AM


QUESTION POSTED AT 27/03/2020 - 10:05 AM